Understanding the socio-economic causes of deforestation: a global perspective - Prochazka, Petr; Abrham, Josef; Cerveny, Jaroslav; Kobera, Lukas; Sanova, Petra; Benes, Daniel; Fink, Julia-Maria; Jiraskova, Eliska; Primasova, Simona; Soukupova, Jana; Smutka, Lubos (Frontiers in Forests and Global Change, 2023)
The global environmental challenges posed by human activities and their impact on the environmental balance have become increasingly evident. This paper investigates the links between deforestation and key economic, social, environmental, and geographical variables. We focus on per capita GDP, total forest cover, and the population across a diverse sample of countries from five continents for the last three decades. The examples of multiple countries spread evenly amongst the continents of Europe, Africa, Asia, and North America. The research focuses on a period ranging from 1990 to 2020. This research aims to shed light on the multinational dynamics of deforestation by investigating the impacts of these variables on deforestation. The findings reveal a significant yet complex interaction between forest cover and social and economic development across the sample countries, highlighting the need for targeted interventions and sustainable land management practices to address deforestation effectively.